Synthesis and behaviour of small RNA species of CHO cells submitted to a heat chick. - Bouche, G (1981)
Incubation of Chinese hamster ovary (CHO) cells for 1 hour at 43 degrees C results in an inhibition of high molecular weight RNA synthesis while most of the ow molecular weight RNAs are still synthesized. In cells returned to 37 degrees C, the transcription of high molecular weight RNA is reinitiated after 7 h recovery. The synthesis of snRNA A, C, D which are transcribed by RNA polymerase B (II) is inhibited in cells incubated at 43 degrees C while the synthesis of 4S, 5S, L and K components is not affected. During the recovery period the synthesis of low molecular weight RNA is increased variously according to the components relative to control cells : x 1.5 for 5S RNA to x 8 for snK. After 9 h recovery at 37 degrees C, snA and SnD are again synthesized but newly synthesized snC does not appear in the nucleus while a putative preC component accumulates in the cytoplasm. On the other hand, the distribution of all the pre-existing low molecular weight RNAs is not affected by the heat shock.